Peningkatan Keterampilan Menulis Puisi Naratif Menggunakan Metode Quantum Learning Berbantuan Media Gambar Berseri - Tiara Rismayanti; Ismaya, Erik Aditya Ismaya; Fathurohman, Irfai Fathurohman (P2M STKIP Siliwangi, 2024)
This classroom action research aims to describe the improvement in student learning outcomes in narrative poetry writing skills using the quantum learning method assisted by series of image media in class IV Indonesian at SDN 3 Jati Kulon. This Classroom Action Research (PTK) was carried out in 2 cycles, each cycle consisting of 2 meetings. Each cycle includes planning, observation, implementation, and reflection. Data collection techniques in this research are interviews, observation, documentation and tests.  The test used is a written test to determine narrative poetry writing skills. The research results show an increase in the skills of writing narrative poetry using the quantum learning method assisted by serial image media. This can be proven by the significant increase in narrative poetry writing test results. In cycle I, it showed that 13 students (61.9%) had achieved learning completeness, and in cycle II it increased to (85.7%) with 18 students who had completed it. It can be concluded that the use of the quantum learning method assisted by serial image media can improve the narrative poetry writing skills of class IV students at SDN 3 Jati Kulon.